Uma avaliação em profundidade do Programa Criança Feliz no estado do Ceará: reconstrução da trajetória institucional e seus significados sob o olhar dos gestores (as) - Monteiro, Ulisses Cruz (2024)
The main objective of this work is to conduct an in-depth analysis of the institutional trajectory of the Criança Feliz Program (PCF) in the State of Ceará, exploring its implementation, the challenges faced, and the meanings attributed by the responsible managers. The central focus of the research is to assess the fulfillment of the program’s goals, which aim to promote comprehensive child development and strengthen parenting in families living in extreme social vulnerability. The Criança Feliz Program is a federal public policy with an intersectoral approach, designed to serve children up to six years old, pregnant women, and their families, with special attention to those benefiting from the Continuous Cash Benefit (BPC) and the Bolsa Família Program. The dissertation also discusses the context in which the PCF was created, as well as the difficulties encountered during its implementation both at the national level and in the State of Ceará. The study seeks to trace the program’s trajectory and conduct a critical analysis of its effectiveness in achieving the established goals. The methodology employed is predominantly qualitative, based on the in depth evaluation approach proposed by Rodrigues (2008; 2011), which offers a detailed and multidimensional analysis of public policies. Semi-structured interviews were conducted with state managers of the PCF, responsible for coordinating the program in different municipalities in Ceará. The research also included a documentary analysis of secondary data and was supported by a theoretical foundation based on legislation and academic studies on public policies focused on early childhood. The results indicate that, despite the challenges faced during the PCF’s implementation, such as limited resources and difficulties in intersectoral coordination, the program was successful in Ceará. This success is largely attributed to the engagement and leadership of state managers, who demonstrated a strong commitment to the program’s execution, even in the face of significant obstacles. Ceará has become a national reference in meeting the PCF’s goals, promoting child development in areas of extreme vulnerability. One of the key factors for the program's success was its intersectoral nature, involving areas such as social assistance, health, and education. This integration model, while demanding in terms of coordination, was essential to ensuring that the families served had access to essential services, strengthening family bonds and promoting child development at a critical stage. Another important aspect was the continuity of home visits, conducted by program agents, which proved crucial for the success of the interventions. These visits made it possible to serve millions of children and pregnant women in Ceará, ensuring the achievement of the proposed goals. The dissertation concludes that the Criança Feliz Program was effective in the State of Ceará, becoming a model for public policies aimed at early childhood. The program's success was attributed to political leadership and the commitment of local managers, along with the recommendation that continuous evaluation of the PCF is essential to ensure its long-term effectiveness. The research suggests that the PCF’s intersectoral model could inspire similar policies in other regions of Brazil, contributing to public policies that serve early childhood.